N $$ \mathcal{N} $$ = 1 Super-Yang-Mills theory on the lattice with twisted mass fermions - Marc Steinhauser; André Sternbeck; Björn Wellegehausen; Andreas Wipf (Journal of High Energy Physics, 2021)
Abstract Super-Yang-Mills theory (SYM) is a central building block for supersymmetric extensions of the Standard Model of particle physics. Whereas the weakly coupled subsector of the latter can be treated within a perturbative setting, the strongly coupled subsector must be dealt with a non-perturbative approach. Such an approach is provided by the lattice formulation. Unfortunately a lattice regularization breaks supersymmetry and consequently the mass degeneracy within a supermultiplet. In this article we investigate the properties of N $$ \mathcal{N} $$ = 1 supersymmetric SU(3) Yang-Mills theory with a lattice Wilson Dirac operator with an additional parity mass, similar as in twisted mass lattice QCD. We show that a special 45° twist effectively removes the mass splitting of the chiral partners. Thus, at finite lattice spacing both chiral and supersymmetry are enhanced resulting in an improved continuum extrapolation. Furthermore, we show that for the non-interacting theory at 45° twist discretization errors of order O a $$ \mathcal{O}(a) $$ are suppressed, suggesting that the same happens for the interacting theory as well. As an aside, we demonstrate that the DDαAMG multigrid algorithm accelerates the inversion of the Wilson Dirac operator considerably. On a 163 × 32 lattice, speed-up factors of up to 20 are reached if commonly used algorithms are replaced by the DDαAMG.